THE DOCTRINE OF KARMA (KAMMA) IN BUDDHISM AND JAINISM: A COMPARATIVESTUDY - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The word kamma in Pali has multiple meanings. The phrase "action or deed" is meant literally. "Good and bad volition" is the commonly understood interpretation (Kusala Akusala Cetana). The law of moral causation, also known as "action (Kamma) and reaction (Vipaka) in the ethical realm," is based on kamma. Most deliberate acts are referred to as kammas. The Buddha and Arahants are the exceptions; they have destroyed all of their passions and so do not accumulate new Kamma. However the Buddha was the one who developed and provided a thorough explanation of the Kamma and Rebirth doctrine found in the old Buddhist writings. The Karma doctrine of the Jaina is unique. Jains believe that thoughts and deeds attract karma and that an individual's current quality of life is determined by his past actions, in contrast to Hindus who see karma as simply the law of nature. According to Jainism, karma is a material substance that pervades the entire cosmos. These karma particles stick to the soul, also known as the jiva, and are carried from one life to the next. Jains strive for emancipation by eliminating all karma associated with the jiva in order to break free from the cycle of rebirth. They achieve this by keeping their word and leading morally and physically upright lives.